Resi-Rise Skyscraper - Susan Kolatan; William MacDonald (Oz, 2002)
The resi-rise is less “building,” more “vertical urbanism.” Its frame, not unlike a spatial matrix of “lots,” is initially built-out to the maximum allowable zoning envelope with deformations accounting for site influences, such as views and adjacencies.